SOSIALISASI PENTINGNYA PARENTING DALAM PEMBENTUKAN KARAKTER ANAK DI DESA PADANGJAYA - Alwi Sofyan; Alfi Muklis Kurniawan; Agnes Rosaliana (Universitas Muhammadiyah Manado, 2021)
Parenting socialization activities regarding the importance of intellectual and character education in dealing with the times are to introduce and socialize true parenting education for the community. Thus, socialization participants are expected to be able to practice the material socialized to their children in everyday life, so that a generation with intellectual and character is produced. The socialization was carried out using direct observation, interviews, and socialization methods, by means of: lectures/providing information and training. As a result of these activities, participants gain knowledge related to parenting; and commit to practice it with their own children.